Unzureichende Umsetzung des Mindestlohns bei Minijobbern - Toralf Pusch; Hartmut Seifert (Wirtschaftsdienst, 2017)
Mit der Einführung des Mindestlohns im Januar 2015 sollten Geringverdiener bessergestellt werden. Da insbesondere Minijobber gering entlohnt werden, ist es aufschlussreich, die Umsetzung des gesetzlichen Mindestlohns in diesem Bereich zu analysieren. Es zeigt sich, dass der gesetzliche Mindestlohn 2015 bei knapp der Hälfte der Minijobber umgangen wurde. Diese Ergebnisse signalisieren, dass eine wirksame Kontrolle zur Verhinderung von Mindestlohnverstößen erforderlich ist. – – In this article, we examine the implementation of the statutory minimum wage of exteuro8.50 per hour for marginal employees ('mini- jobbers') in Germany. Using two representative datasets, it can be shown that six months after the law came into force about 45% of marginal employees still received wages below the minimum wage threshold. Minimum wage violations are especially prevalent in lowwage sectors such as the hotel and catering sector (70%) and retail (52%), as well as in small establishments (58%). The minimum wage improved the wage situation in Germany, but the large number of violations suggest that more effective public controls are needed.
Keywords: J38; J70; J80; 330